Letter - Deptford and Greenwich Trades Council, 5 May 1926 (Deptford)
1926-05-05 "Letter - Deptford and Greenwich Trades Council, 5 May 1926" [g0186001.jpg], 5 May 1926, Deptford and Greenwich Trades Council Local Organisation